The Role of the Principal in Increasing Teacher Performance Through Periodic Academic Supervision - Muhammad Saleh; Mutiani Mutiani (STAI Hubbulwathan Duri, 2021)
This research aims to describe the ideal role of the principal in carrying out academic supervision. A qualitative approach with a descriptive method is used in the research. Observations were made at SMP Negeri 1 Tamiang Layang, structured interviews with 12 teachers, and researchers carried out the collection of documentation. The data analysis technique used is the Miles and Huberman interactive model. Researchers used the triangulation technique to obtain redundant data. The results of the study describe the principal's academic supervision carried out in three main activities, namely; 1) planning stage; 2) implementation stages that refer to academic Supervision Development Module in the Implementation of the 2013 Curriculum of the Ministry of Education and Culture in 2018; and 3) follow-up stages as a form of input for improving teacher performance in providing learning. These three activities are a series of systematic activities that cannot be separated from each other. The role of the principal is emphasized in the pattern of coaching. It is because teachers are considered partners who can be invited to exchange ideas about various problems at school.